Drug delivery systems based on iron oxide magnetite-layered double hydroxide nanoparticles for liver anti-cancer drugs - Ebadi, Mona (2021)
The current strategy for cancer treatment focuses on anti-cancer drugs but they have inimitable problems because of adherence to healthy cells. In chemotherapy, if the effect of the medication is specifically restricted to the target cells, it can significantly reduce these detrimental effects. Lately, iron oxide nanoparticles (FNPs) have received much attention for targeted drug delivery. It has been shown that the chemical binding of the drug to the magnetic nanoparticles which are coated by a biodegradable polymer such as polyethylene glycol (PEG) and polyvinyl alcohol (PVA) and carried by a nanocarrier like layered double hydroxides (LDHs) is a reliable method of delivering the drug. The purpose of this work is to develop a controlled release anti-cancer drug formulation. For this purpose, FNPs as the core was coated with different biocompatible polymers such as PEG and PVA, and also co-coated by two types of nanocarriers; layered double hydroxides (Mg/Al-LDH and Zn/Al-LDH) as the shell, loaded with different anti-cancer drugs; 5-fluorouracil (5-FU) and sorafenib (SO). Both active drugs were encapsulated separately onto iron oxide which is coated with PEG or PVA and Mg/Al-LDH or Zn/Al-LDH to form 8 different magnetic nanoparticles; iron oxide-polyethylene glycol-5-fluorouracil-Mg/Al-LDH (FPEGFU-MLDH), iron oxide-polyethylene glycol-5-fluorouracil-Zn/Al-LDH (FPEGFU-ZLDH), iron oxide-polyvinyl alcohol-5-fluorouracil-Mg/Al-LDH (FPVAFU-MLDH), iron oxide-polyvinyl alcohol-5-fluorouracil-Zn/Al-LDH (FPVAFU-ZLDH), iron oxide-polyethylene glycol- sorafenib-Mg/Al-LDH (FPEGSO-MLDH), iron oxide-polyethylene glycol-sorafenib- Zn/Al- LDH (FPEGSO-ZLDH), iron oxide-polyvinyl alcohol-sorafenib-Mg/Al-LDH (FPVASO-MLDH) and iron oxide-polyvinyl alcohol-sorafenib-Zn/Al-LDH (FPVASO-ZLDH), respectively. The results of XRD, TGA, and FTIR analyses of the magnetic nanoparticles showed the presence of the coating layers on the surface of the FNPs for all the as-synthesized samples. The VSM analysis showed that the magnetic nanoparticles retain their superparamagnetic property. FESEM, DLS, and HRTEM, and it was found that the sizes of all the synthesized nanoparticles were in the nanoscale range. The coating effect on a drug release, the loading efficiency, and percentage loading of drugs were also investigated using the HPLC and UV-Vis in two different phosphate buffer solutions at pH 4.8 and 7.4 and demonstrated that polymer coverage was one of the effective strategies in controlling the drug release and enhanced the percentage of drug loading. The cytotoxicity studies revealed that the anticancer nanodelivery systems show a much better anticancer activity of the magnetic-based nanoparticles compared to their counterparts, the free drugs on HepG2 cells. At the same time, it also found that the nanoparticles are less toxic compared to the normal fibroblast, 3T3 cells. Based on the results obtained in this work, the novel co-coated magnetic nanoparticles with two carriers were found to be suitable for drug delivery. It is anticipated that the nanoparticle developed in this work is non-toxic, non-immunogenic, biocompatible, biodegradable, and has a longer retention time in the body, therefore improve efficacy and bioavailability.